Foliar epidermal characters in the genus brachystegia benth (2000)
The study reports on the structure of trlchomes, epidermal cells and stomata, the trlchomes are nonglandular, unicellular pointed or bent and long or short. The epidermal cells are variously shaped and stomata are paracytic and amphistomatic.